(x+1)(x-1)(x²+x+1)(x²-x+1)

Question

(x+1)(x-1)(x²+x+1)(x²-x+1)

in progress 0
Eirian 4 years 2020-11-04T16:01:46+00:00 2 Answers 51 views 0

Answers ( )

    0
    2020-11-04T16:03:00+00:00

    Đáp án: `x^6-1`

     

    Giải thích các bước giải:

    `(x+1)(x-1)(x^2+x+1)(x^2-x+1)`

    `=[(x+1)(x^2-x+1)].[(x-1)(x^2+x+1)]`

    `=(x^3+1)(x^3-1)`

    `=(x^3)^2-1`

    `=x^6-1`

    0
    2020-11-04T16:03:12+00:00

    `(x+1)(x-1)(x^2+x+1)(x^2-x+1)`

    `=[(x+1)(x^2-x+1)][(x-1)(x^2+x+1)]`

    `=(x^3+1)(x^3-1)=x^6-1`

     

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )